Reverse brain drain – a real threat or a speculative narrative? The case of the United Kingdom and the United States - Banaś, Monika (SocietàMutamentoPolitica, 2018)
This article constitutes an attempt to conduct a cultural studies analysis of the issue/phenomenon known as ‘reverse brain drain’ (the outflow of highly qualified and specialised workers from highly developed countries). The field of analysis has been restricted to the markets of the United Kingdom and the United States, countries standing on the threshold of major changes caused by preparations for the UK leaving the structures of the EU and the highly controversial figure of Donald Trump assuming the office of US president, respectively.